Diagnosis and management of lower respiratory tract infections. Issue 5 (5th March 2014) - Rodrigo, Chamira; Lim, Wei Shen
Abstract Lower respiratory tract infections in the community lead to considerable morbidity and days off work. Our Drug review considers the assessment of disease severity, when to prescribe antibiotics and recommended management of LRTIs, followed by sources of further information.